Standardized butanol fraction of WIN-34B suppresses cartilage destruction via inhibited production of matrix metalloproteinase and inflammatory mediator in osteoarthritis human cartilage explants culture and chondrocytes - Huh Jeong-Eun; Seo Byung-Kwan; Baek Yong-Hyeon; Lee Sanghoon; Lee Jae-Dong; Choi Do-Young; Park Dong-Suk (BMC, 2012)
Abstract Background WIN-34B is a novel Oriental medicine, which represents the n-butanol fraction prepared from dried flowers of Lonicera japonica Thunb and dried roots of Anemarrhena asphodeloides BUNGE. The component herb of WIN-34B is used for arthritis treatment in East Asian countries. The aim of this study was to determine the cartilage-protective effects and mechanisms of WIN-34B and its major phenolic compounds, chlorogenic acid and mangiferin, in osteoarthritis (OA) human cartilage explants culture and chondrocytes. Methods The investigation focused on whether WIN-34B and its standard compounds protected cartilage in interleukin (IL)-1β-stimulated cartilage explants culture and chondrocytes derived from OA patients. Also, the mechanisms of WIN-34B on matrix metalloproteinases (MMPs), tissue inhibitor of matrix metalloproteinases (TIMPs), inflammatory mediators, and mitogen-activated protein kinases (MAPKs) pathways were assessed. Results WIN-34B was not cytotoxic to cultured cartilage explants or chondrocytes. WIN-34B dose-dependently inhibited the release of glycosaminoglycan and type II collagen, increased the mRNA expression of aggrecan and type II collagen, and recovered the intensity of proteoglycan and collagen by histological analysis in IL-1β-stimulated human cartilage explants culture. The cartilage protective effect of WIN-34B was similar to or better than that of chlorogenic acid and mangiferin. Compared to chlorogenic acid and mangiferin, WIN-34B displayed equal or greater decreases in the levels of MMP-1, MMP-3, MMP-13, ADAMTS-4, and ADAMTS-5, and markedly up-regulated TIMP-1 and TIMP-3. WIN-34B inhibited inflammatory mediators involved in cartilage destruction, such as prostaglandin E2, nitric oxide, tumor necrosis factor-alpha, and IL-1β. The phosphorylation of extracellular signal-regulated kinase, c-Jun N-terminal kinase (JNK), and p38 was significantly reduced by WIN-34B treatment, while phosphorylation of JNK was only inhibited by chlorogenic acid or mangiferin in IL-1β-stimulated chondrocytes. Conclusions WIN-34B is potentially valuable as a treatment for OA by virtue of its suppression of MMPs, ADAMTSs, and inflammatory mediators, and it's up-regulation of TIMP-1 and TIMP-3 involved in the MAPK pathway.